Exposure of medical students to sexism and sexual harassment and their association with mental health: a cross-sectional study at a Swiss medical school - Carole Clair; Joelle Schwarz; Alexandre Berney; Valerie Carrard; Sylvie Berney; Jeanne Marie Barbier (BMJ Open)
Objectives To assess the self-reported prevalence of sexism and sexual harassment at a Swiss medical school, and to investigate their association with mental health. Research hypotheses were an association between sexism/sexual harassment and poor mental health and a higher prevalence of sexism/sexual harassment in clinical rotations.Design Cross-sectional study as a part of ETMED-L project, an ongoing cohort study of interpersonal competences and mental health of medical students.Setting Single-centre Swiss study using an online survey submitted to medical students.Participants From 2096 registered students, 1059 were respondents (50.52%). We excluded 26 participants (25 due to wrong answers to attention questions, and 1 who did not answer the sexism exposure question). The final sample (N=1033) included 720 women, 300 men and 13 non-binary people.Measures Prevalence of self-reported exposure to sexism/sexual harassment. Multivariate regression analyses of association between being targeted by sexism or sexual harassment and mental health (depression, suicidal ideation, anxiety, stress, burnout, substance use and recent mental health consultation). Regression models adjusted for gender, academic year, native language, parental education level, partnership and an extracurricular paid job.Results Being targeted by sexism or sexual harassment was reported by 16% of participants with a majority of women (96%). The prevalence increased with clinical work. After adjusting for covariates, we found association between being targeted by sexism/harassment and risk of depression (OR 2.29, 95% CI 1.54 to 3.41, p<0.001), suicidal ideation (B coefficient (B) 0.37, p<0.001) and anxiety (B 3.69, p<0.001), as well as cynicism (B 1.46, p=0.001) and emotional exhaustion (B 0.94, p=0.044) components of burnout, substance use (B 6.51, p<0.001) and a recent mental health consultation (OR 1.78, 95% CI 1.10 to 2.66, p=0.005).Conclusions Sexism and sexual harassment, although less common than usually reported, are behaviours of concern in this medical school and are significantly associated with mental health.